2009
DOI: 10.1007/s10048-009-0218-9
|View full text |Cite
|
Sign up to set email alerts
|

Broad clinical phenotypes associated with TAR-DNA binding protein (TARDBP) mutations in amyotrophic lateral sclerosis

Abstract: (Max 150 words)The finding of TDP-43 as a major component of ubiquitinated protein inclusions in amyotrophic lateral sclerosis (ALS) has led to the identification of 30 mutations in the TARDBP gene, encoding TDP-43. All but one are in exon 6, which encodes the glycinerich domain. The aim of this study was to determine the frequency of TARDBP mutations in a large cohort of motor neurone disease (MND) patients from Northern England (42 non-SOD1 FALS, 9 ALS-FTD, 474 SALS, 45 PMA cases). We identified 4 mutations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 35 publications
0
34
0
3
Order By: Relevance
“…Because significant neuronal loss was only seen in brain neurons but not in spinal cord motor neurons, it appeared that behavior deficits in hemizygous TDP-43 M337V mice, including poor rotarod or beam-walking performance, were likely caused by dysfunction or loss of brain neurons rather than spinal cord motor neurons. Although some studies showed the absence of dementia in patients bearing the M337V mutation, 7,25 one study from Kirby et al 26 reported intellectual impairment in a patient from a family bearing the M337V mutant with very early disease onset at 2.5 years of age. In fact, some TDP-43 mutations have been identified in FTD patients without motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because significant neuronal loss was only seen in brain neurons but not in spinal cord motor neurons, it appeared that behavior deficits in hemizygous TDP-43 M337V mice, including poor rotarod or beam-walking performance, were likely caused by dysfunction or loss of brain neurons rather than spinal cord motor neurons. Although some studies showed the absence of dementia in patients bearing the M337V mutation, 7,25 one study from Kirby et al 26 reported intellectual impairment in a patient from a family bearing the M337V mutant with very early disease onset at 2.5 years of age. In fact, some TDP-43 mutations have been identified in FTD patients without motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…From the data available, it is evident that combining different MR imaging modalities that are sensitive to different aspects of ALS pathology (eg, motor and extramotor) is a promising way to further increase our understanding of the mechanisms accounting for the accumulation of irreversible disability in this condition. Moreover, the emerging scenario from genetic studies indicates a consistent overlap between the pathogenetic changes in most forms of sporadic and familial ALS, [108][109][110] thus suggesting that the application of neuroimaging in familial patients with ALS may allow identification of abnormalities that can hopefully be translated to the assessment of sporadic ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of TARDBP have been identified as a disease protein in ubiquitin-positive, τ-, and α-synuclein-negative frontotemporal dementia (FTLD-U) and in amyotrophic lateral sclerosis (ALS) [2,3]. Over the past years, 44 mutations in TARDBP have been reported in 5% of non- SOD1 familial ALS (FALS) and 0.4% of sporadic ALS (SALS) [4,5] and, more rarely, in cases with frontotemporal dementia (FTD) [6], Parkinson's disease [7] and Alzheimer's disease [8]. Most of the reported mutations are missense mutations that occur in the highly conserved C-terminus of TARDBP , which encodes the exon 6 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypically, ALS patients with TARDBP mutations may present with limb or bulbar onset [12,13]. There is however considerable variation in age of onset and rapidity of disease course [4]. …”
Section: Introductionmentioning
confidence: 99%